The market of tourism services and its potential for development in the municipalities of Złocieniec and Drawsko Pomorskie (Poland) (Geography and Tourism, 2018)
High competition in the tourism market services requires conducting marketing activities based on cooperation between entities in a given area. The paper aims to investigate the current state of tourism market services in the municipalities of Złocieniec and Drawsko Pomorskie and to analyze their potential for development. The Sokal-Michner coefficient was used and a review of key strategy papers was provided. The study concluded that Złocieniec and Drawsko Pomorskie municipalities have a very high potential for tourism and that it is not fully realized. Their offer includes sustainable, green as well as qualified tourism. Underdeveloped transport and tourism infrastructure impede tourism development of the municipalities considered. Both municipalities have the necessary potential for tourism development: natural values, geographic location, and cultural values. Tourism provides an opportunity for economic growth for those municipalities.